An Investigation on the Mechanical Properties of Cement Mortar under Axial Loading Conditions at High Temperature. Issue 2 (April 2021) - Gao, Zhifei; Wang, Linbing; Yang, Hailu
Abstract: Concrete preloaded during heating always shows higher compressive strength than that unloaded, and the reason was confused. As one of the main components of concrete, cement mortar has an important impact on the performance of concrete at high temperatures. However, few studies have conducted on the stressed mechanical properties strength of mortar at high temperature. In this paper, a series of mechanical tests were conducted to investigate the mechanical properties of cement mortar specimens under axial loading conditions. Seven temperatures (20 °C, 100 °C, 200 °C, 300 °C, 400 °C, 500 °C, 600 °C) and three pre stress ratios (0.2, 0.4, 0.6) were set during the in-door laboratory tests. Test results showed that temperature and pre-stress have significant influences on the compressive strength and the failed mode of cement mortar specimens at high temperature. The compressive strength of mortar under stressed condition was even higher than that at room temperature which might be a reason for the improvement of stressed compressive strength.